Sustainable Polymers: Sustainable Polysulfides for Oil Spill Remediation: Repurposing Industrial Waste for Environmental Benefit (Adv. Sustainable Syst. 6/2018). (19th June 2018) - Worthington, Max J. H.; Shearer, Cameron J.; Esdaile, Louisa J.; Campbell, Jonathan A.; Gibson, Christopher T.; Legg, Stephanie K.; Yin, Yanting; Lundquist, Nicholas A.; Gascooke, Jason R.; Albuquerque, Inês S.; Shapter, Joseph G.; Andersson, Gunther G.; et al.
Abstract : In article number1800024 Justin Chalker and co‐workers prepare a sustainable oil sorbent from waste cooking oil and sulfur, a by‐product of petroleum refining. The sorbent absorbs crude oil upon contact and forms an aggregate that can be removed by skimming or filtration. The oil can be recovered by mechanical compression and the polymer can be re‐used. The study is an advance in waste valorisation and environmental remediation.